Liquid–liquid core–shell configurable mesoscale spherical acoustic lens with subwavelength focusing; Applied Physics Express; Vol. 12, iss. 8 - Perez-Lopez S. Sergio; Candelas P. Pilar; Fuster J. M. Jose Miguel; Rubio C. Constanza; Minin O. V. Oleg Vladilenovich; Minin I. V. Igor Vladilenovich (2019, 2019)
Title screen